Analisa Kuat Lentur Perkerasan Menggunakan Alat Benkelman Beam Pada Ruas Jalan Perintis Kemerdekaan - Satriyani Okbri (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
AbstractThe city of Palembang as a Metropolitan city has a greater population density and it affects the increase in vehicle volume up to 20% / year. to anticipate the increase in the volume of vehicles on the Palembang Kemersungan Printis Road section, sharing the ways of the government one of them was the construction of new roads, widening roads, maintenance and repair of roads and overlays. The design of flexible pavement added thick layer that is commonly used at this time using the deflection method. The deflection method in this study uses traffic volume data which will then be analyzed to obtain the standard axle load equivalent (CESA) accumulation value over the life of the plan. Deformation values can be obtained from the Benkelman Beam tool testing results. This study aims to determine the relationship between measurements of road surface conditions with deflection values